Enhancement of return loss and gain using 10mm air-cut technique for integrated SIW filtenna / Nurul Syafeeqa Ishak - Ishak, Nurul Syafeeqa (2017)
This paper presents a design of integrated substrate integrated waveguide (SIW) filter and microstrip antenna using multilayer approach at the nearest frequency of 2.38GHz. The design has been using Roger RT/Duroid 5880 with permittivity of £r =2.2 and a thickness of 0.787mm as a substrate. The design has been simulated using Computer Simulation Technology. It is based on the circular cavity structure using TMoio mode for the filter and TMno mode for the antenna. Both design techniques of SIW filter and microstrip antenna are coupled by rectangular iris at the common ground plane. However, losses are the main factor in SIW technology. The decreasing in dielectric loss will contribute to the reduction of total dissipated power and both filter and antenna response. Thus, to overcome the losses, lower dielectric loss is used by using air (conceptual) as the transmission medium in SIW. The simulation result show good antenna and radiation pattern that prove the capability to integrate SIW filter and microstrip antenna directly without requirement of external matching and also it will reduce the size of the device, thus the 10mm air-cut filtenna has chosen as the best air-cut size as it shows improvement by 15.51% than its recent study.